An investigation of the mechanical properties of metallic lattice structures fabricated using selective laser melting. (August 2018) - Feng, Qixiang; Tang, Qian; Liu, Zongmin; Liu, Ying; Setchi, Rossi
Metallic lattice structures manufactured using selective laser melting are widely used in fields such as aerospace and automobile industries in order to save material and reduce energy consumption. An essential element of metallic lattice structures design is determining their mechanical behaviors under loading conditions. Theoretical method based on beam theory has been proposed for evaluating the behaviors of the commonly used body-centered cubic lattice structures. However, it is difficult to predict theoretically the properties of the uniaxially reinforced lattice structures based on the body-centered cubic structures. Since the reinforced structures have superior strength to weight ratio and are deemed promising in lightweight-design applications, this article proposed a force-method-based theoretical method to calculate the mechanical properties of the body-centered cubic structure and its two types of uniaxially reinforced structures fabricated via selective laser melting. The finite element analysis and compression experiment study of selective laser melting samples made using Ti6Al4V powders demonstrated the validity of the proposed analytical method.